Budgetary changes and organizational performance: Evidence from state transportation agencies. - Chen, Can; Flink, Carla M. (Policy Studies Journal, 2022)
Existing punctuated equilibrium theory (PET) literature identifies the causes of policy punctuations. However, there are a lack of theoretical and empirical studies on the effects of policy punctuations on organizational performance. This study extends PET from policy formulation to policy outcomes and explores how public agencies transfer budgetary inputs to organizational performance outcomes in the policy context of American state highway transportation infrastructure. Based on a longitudinal research design, the research employs a panel two‐way fixed effects regression model to analyze the performance consequences of budgetary changes for 50 states during an almost 20‐year period (1995–2013). The key findings indicate that state expenditure (highway maintenance) changes experience much more friction and volatility over time than performance (acceptable roads) changes. In addition, state highway transportation agencies can mitigate the impact of large budgetary cuts on organizational performance, but do not seem to capitalize on large budgetary gains to improve performance.